Sistem Presensi Mahasiswa Berbasis QR Code di STMIK “AMIKBANDUNG” - Amal Julio Rafila; Tedjo Darmanto; Rudi Kurniawan (LPPM STMIK AMIK BANDUNG, 2020)
One of the important things that need to be considered in student assessment is the problem of student presence. The student attendance process that is very commonly done by universities is recording attendance manually, as currently applied by STMIK